Новая экспозиция Зоологического музея ЦНПМ АН УССР - Щербак, Н.Н. (Вестник зоологии, 1969)
In 1966—1967 the zoological exposition of the museum of the Institute of Zoology of the Ukrainian Academy of Sciences (a constituent part of the Central Scientific-Naturalistic Museum of the Ukrainian Academy of Sciences) was reconstructed. The area of the museum is 1200 m². There almost all the species of the Ukrainian fauna, a great number of species from the USSR fauna and main representatives of the world fauna (altogether 5298 ind.) are exhibited in a systematic order. Data on morphology, origin, ecology (eleven landscape diorams included), practical value and protection of nature are widely used in the exposition. The newest scientific data are combined with a high level of decorative design. Some new methods were applied preparing exhibits and their display. The zoological museum is now the largest museum of such a kind in the Ukraine and one of the best museums in the USSR.